IN SILICO MODELING OF MONOMERIC DEXAMETHASONE-INDUCED RAS-RELATED PROTEIN 1 AND RAS HOMOLOG ENRICHED IN STRIATUM: ROLE OF N TERMINUS AND STRUCTURE‑FUNCTION RELATIONSHIP - Verma, Rashmi; Kumar, Navin; Thapliyal, Ashish (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Dexamethasone-induced Ras-related protein 1 (Dexras1) and Ras homolog enriched in striatum (RHES) are the two monomeric small G proteins that belong to Ras superfamily. These two proteins show 62% similarity. Both of these proteins are involved in signaling and modulation of several pathophysiological processes. They have unique GTP binding domain and a unique C and N terminus. C terminus is known to interact with several proteins; however, the role of its unique N terminus is still not known. The three-dimensional (3D) structure of these proteins is also not available in any of the databases yet. This present study approaches bioinformatics tools and servers to predict the 3D structure of these two proteins in silico. Methods: In this study, two bioinformatics servers were used, namely Swiss modeling server and Iterative Threading ASSEmbly Refinement (I-TASSER) server. Results: Both servers developed many alignment templates of Dexras1 and RHES. These alignments were used to develop 3D structure using Pymol. These models have different regions of proteins such as N terminus, GTP-binding domains, effector loop, C terminus, and the unique CAAX site. The models deduce that the N-terminals of both Dexras1 and RHES are unique regions that might possible be dangling out of the protein while it gets inserted into the membrane. We hypothesize that this unique N-terminal might have a distinct role in the modulation of N-type calcium channels. Conclusion: All the models generated show predicted 3D structure of Dexras1 and RHES protein. This study of structural prediction will be helpful in knowing the interaction of Dexras1 and RHES and a step forward to target these two proteins as a novel therapeutic drug.